Anaemia at admission is associated with poor clinical outcome in cerebral venous thrombosis. (24th January 2020) - Silvis, S. M.; Reinstra, E.; Hiltunen, S.; Lindgren, E.; Heldner, M. R.; Mansour, M.; Ghiasian, M.; Jood, K.; Zuurbier, S. M.; Groot, A. E.; Arnold, M.; Barboza, M. A.; et al.
Abstract : Background and purpose: Anaemia is associated with poor clinical outcome after ischaemic and haemorrhagic stroke. The association between anaemia and outcome in patients with cerebral venous thrombosis (CVT) was examined. Methods: Consecutive adult patients with CVT were included from seven centres. Anaemia at admission was scored according to World Health Organization definitions. Poor clinical outcome was defined as a modified Rankin Scale score 3–6 at last follow‐up. A multiple imputation procedure was applied for handling missing data in the multivariable analysis. Using binary logistic regression analysis, adjustments were made for age, sex, cancer and centre of recruitment (model 1). In a secondary analysis, adjustments were additionally made for coma, intracerebral haemorrhage, non‐haemorrhagic lesion and deep venous system thrombosis (model 2). In a sensitivity analysis, patients with cancer were excluded. Results: Data for 952 patients with CVT were included, 22% of whom had anaemia at admission. Patients with anaemia more often had a history of cancer (17% vs. 7%, P  < 0.001) than patients without anaemia. Poor clinical outcome (21% vs. 11%, P  < 0.001) and mortality (11% vs. 6%, P  = 0.07) were more common amongst patients with anaemia. After adjustment, anaemia at admission increased the risk of poor outcome [adjusted odds ratio (aOR) 2.4, 95% confidence interval (CI) 1.5–3.7, model 1]. Model 2 revealed comparable results (aOR 1.9, 95% CI 1.2–3.2), as did the sensitivity analysis excluding patients with cancer (aOR 2.3, 95% CI 1.3–3.8, model 1). Conclusion: The risk of poor clinical outcome is doubled in CVT patients presenting with anaemia at admission.